Integrating molecular tools into freshwater ecology: developments and opportunities. (28th April 2014) - Pauls, Steffen U.; Alp, Maria; Bálint, Miklós; Bernabò, Paola; Čiampor, Fedor; Čiamporová‐Zaťovičová, Zuzana; Finn, Debra S.; Kohout, Jan; Leese, Florian; Lencioni, Valeria; Paz‐Vinas, Ivan; Monaghan, Michael T.
Summary Molecular genetic techniques have been used in freshwater biology for more than 30 years. Early work focussed on studies of population structure, systematics and taxonomy. More recently, the range of studies has broadened to include ecology and adaptation. Advances in analytical methods and in technology (e.g. next‐generation sequencing) and decreasing costs of data production ensure that the field will continue to develop and broaden in scope. At least three factors make the application of molecular techniques to freshwater biology exciting. First, the highly variable nature of many aquatic habitats makes them excellent models for the study of environmental change on ecological and evolutionary time scales. Second, the mature state of the field of freshwater biology provides an extensive foundation of ecological knowledge of freshwater organisms and their distinct adaptations. Third, the methodological advances allow researchers to focus more on merging molecular and ecological research and less on designing studies around technical limitations. We identified eight research areas in freshwater biology in which the integration of molecular and ecological approaches provides exceptional opportunities. The list is not exhaustive, but considers a broad range of topics and spans the continuum from basic to applied research. The areas identified use a combination of natural, experimental and in silico approaches. With advancing molecular techniques, freshwater biology is in an unusually strong position to link the genetic basis and ecological importance of adaptations across a wide range of taxa, ecosystems and spatiotemporal scales. Our aim was to identify opportunities for the integration of molecular and ecological approaches, to motivate greater collaboration and crossover, and to promote exploitation of the synergies of bridging ecological and evolutionary freshwater research.